Partisipasi Kelas dalam Mata Kuliah Akuntansi: Persiapan, Frekuensi, Kenyamanan dan Pembelajaran - Paskah Ika Nugroho; Agung Lestari (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
This study aims to examine the factors that influence students’ comfort to participate in the class, and their impact on the objective measure of learning. This study uses an active learning method, which focuses on the case discussions in the management accounting class at Satya Wacana Christian University. This research obtains the data on students' initial habits and perceptions of class discussions through pre and post-test questionnaires. Furthermore, the objective measure of learning was based on students’ marks obtained from lecturers. Three marks were recorded for each student: the final exam, the case discussion, and the class participation marks. Hypothesis testing is done using multiple regression analysis. The test results show that the frequency of student participation in class discussions has a positive effect on the students’ comfort to participate in the class. The result also indicates that students’ comfort and initial GPA have a positive effect on the objective measures of students’ learning.